2016
DOI: 10.1177/1091581816646973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Mouse Model of Oral Potassium Cyanide Intoxication

Abstract: Potassium cyanide (KCN) is an inhibitor of cytochrome C oxidase causing rapid death due to hypoxia. A well-characterized model of oral KCN intoxication is needed to test new therapeutics under the Food and Drug Administration Animal Rule. Clinical signs, plasma pH and lactate concentrations, biomarkers, histopathology, and cyanide and thiocyanate toxicokinetics were used to characterize the pathology of KCN intoxication in adult and juvenile mice. The acute oral LD50s were determined to be 11.8, 11.0, 10.9, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…The experimental approaches we used produced effects that are extremely close to those produced by an acute CN intoxication by ingestion (10, 11). These forms of poisoning are regarded as a potential source of intoxication during a criminal act or a potential terrorist attack.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The experimental approaches we used produced effects that are extremely close to those produced by an acute CN intoxication by ingestion (10, 11). These forms of poisoning are regarded as a potential source of intoxication during a criminal act or a potential terrorist attack.…”
Section: Discussionmentioning
confidence: 96%
“…These forms of poisoning are regarded as a potential source of intoxication during a criminal act or a potential terrorist attack. Recent studies in rodents (10, 11) have established how rapidly lethal can oral intoxication be (within minutes). These effects are very well mimicked by an IP injection since during both oral or IP administration, the diffusion of CN into the blood does not depend on the level of breathing and CN will continue to diffuse at the same rate regardless of the levels of minute ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In that study, the authors determined the LD 50 of oral cyanide in these mice, noted that the natural history of oral cyanide toxicity is similar in mice and humans, and concluded that a reproducible small animal model can be used to test potential countermeasures for oral cyanide toxicity. A limitation of the cited study 22 is the use of a small animal model, where monitoring of cardiovascular parameters can prove to be challenging. In addition, given the large size difference between mice and humans, scaling the dose of any potential therapeutics might be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…HCN is formed more favorably in an acidic milieu after the ingestion of cyanide salts such as KCN, and these differences in pH may explain potential differences in the toxic response to oral cyanide exposure across species. [20][21][22] In studies using animals to model human toxicity, the use of moderate-sized species such as rabbits, offers various advantages compared with smaller animals, such as mice. For example, rabbits are more amenable to cardiovascular monitoring in real-time than are mice.…”
Section: Discussionmentioning
confidence: 99%